회장루 보유자의 마음챙김명상을 접목한 회복탄력성 증진 프로그램 개발 및 효과 - 신지혜; 최자윤; Shin, Jee Hye; Choi, Ja Yun (Journal of Korean Academy of Nursing, 2021)
Purpose: The purpose of this study was to develop a resilience enhancement program applying mindfulness meditation (REP-MM) and evaluate the effects of the program on post-traumatic stress (PTS), resilience, and health-related quality of life (HRQoL) in patients with ileostomy. Methods: The REP-MM was developed by combining the resilience enhancement program with mindfulness meditation according to four patterns. The program was developed through identifying patients' needs, reviewing relevant literature, developing a preliminary program, and testing content validity and user evaluation. The participants were 55 patients with ileostomy. We conveniently assigned 27 patients to the experimental group and 28 to the control group. The study was conducted in conducted in a hospital from January 22 to May 30, 2019. The REPMM was provided to the experimental group, and conventional ileostomy care was provided to the control group using a nonequivalent control-group pretest-posttest design. Results: ANCOVA revealed that the levels of PTS (F = 321.64, p < .001), resilience (F = 111.86, p < .001), and HRQoL (F = 31.08, p < .001) in the experimental group were higher than those in the control group when comparing pretest to posttest changes. Conclusion: The REP-MM is effective in PTS, resilience, and HRQoL in patients suffering from post-stoma creation crisis. The REP-MM can induce positive self-recognition changes in patients with ileostomy through dispositional, situational, relational, and philosophical interventions. We suggest nurses reduce PTS and improve resilience and HRQoL in patients with ileostomy.